The Symbolic and Aesthetic Value of Traditional Tableware: A Systematic Review - Victor M I Mambraku; Nuning Yanti Damayanti; Yannes Martinus Pasaribu; Adhi Nugraha (Dinasti Publisher, 2025)
Traditional tableware reflects significant symbolic and aesthetic values that help maintain cultural identity in the era of globalization. However, the shift towards modern products has reduced the role of traditional tableware, leading to a decline in people's understanding of its cultural significance. The study analyzed the literature that highlights the role of traditional tableware in various cultures, focusing on its spiritual, social, and ecological aspects. Using a systematic approach, this study identifies sustainable education and design-based preservation strategies that uphold the symbolic meanings of traditional tableware. Our methods include the analysis of literature and cross-cultural perspectives of different ethnicities. We highlight the importance of integrating traditional tableware into modern education and design to strengthen people's connection to their cultural identity. Our findings suggest that cultural preservation can be enhanced by promoting aesthetics, revitalizing symbolic values, and adopting an ecology-based approach that supports the sustainability of local cultural identity. The study proposes a conceptual framework that guides cultural preservation strategies in the face of the challenges of globalization, offering practical implications for education and product design relevant to modern society.